Occupational-Related Exposure to Diesel Exhaust and Kidney Cancer: Systematic Review and Meta-Analysis of Cohort Studies - Collatuzzo, Giulia; Teglia, Federica; Boffetta, Paolo (La Medicina del Lavoro, 2025)
Background: The association between diesel exhaust and cancer other than the lung is not well established. We aimed to conduct a systematic review and meta-analysis on the association between diesel and kidney cancer in workers.Methods: Two trained researchers conducted a systematic review to identify cohort studies examining the relationship between occupational exposure to diesel exhaust and the risk of cancer other than lung cancer. Of the 43 retained studies, 15 reported information on kidney cancer. We performed random-effects meta-analyses for ever-exposure to diesel exhaust. Summary relative risks (RR) and 95% confidence intervals (CI) were calculated for the association between diesel exhaust exposure and kidney cancer. Results: Overall, the RR of kidney cancer was 1.08 (95% CI=1.01-1.15, heterogeneity p=0.1, I2=28.6%). The summary RR was 1.08 for incidence (95% CI=1.01-1.16; I2=36.7%) and 1.09 for mortality (95% CI=0.92-1.30, I2=14.5%), p of heterogeneity=0.914. The summary RR of European studies was 1.08 (95% CI=1.00-1.16, I2=37.8 %), that of USA/Canada studies was 1.10 (95% CI=0.94-1.29, I2=8.5%), p of heterogeneity=0.837. Publication bias was not detected. Conclusions: Workers exposed to diesel exhaust may experience an increased risk of developing kidney cancer, although the evidence is not entirely consistent, and residual confounding cannot be excluded.